Faktor-Faktor yang Berhubungan dengan Kejadian Low Back Pain (LBP) Pada Pekerja di PLTU NII Tanasa Kendari - Illahi, Muhammad Alim Anugrah; Pratiwi, Arum Dian; H, Siti Nurfadillah (Universitas Malahayati, 2024)
ABSTRACT Low Back Pain (LBP) can be defined as persistent pain between the waist and the crease of the buttocks. LBP is also one of the PAKs, especially for workers. The causes of LBP are very broad and difficult to detect, but in fact the causes of LBP in the workplace are mostly ergonomic problems or incorrect working positions. Based on observations during internship activities at PLTU Nii Tanasa Kendari, low back pain is often heard as a complaint by workers who work in a long sitting position. Low back pain is one of the work-related diseases that dominates workers at PLTU Nii Tanasa Kendari and one that has quite a detrimental impact on the company and its suffering, with disruption of activities while working, disruption of concentration while working, back pain in the back. felt while working, even after work. This type of research is quantitative research and is analytical research that is observational in nature. This study used a cross sectional research design. The research sample was 87 people. Data obtained by creating a questionnaire were analyzed using the Chi-square test. The results of the study showed that there was a relationship between sitting position and the incidence of Low Back Pain (p=0.001), there was no association between the length of sitting and the incidence of Low Back Pain (p=0.297), there was no association between working period and the incidence of Low Back Pain (p =0.105), there is no relationship between BMI and the incidence of Low Back Pain (p=0.451), and there is no association between disease history and the incidence of Low Back Pain (p=0.791). It is hoped that new researchers can further explore the incidence of Low Back Pain. Keywords: Lower Back Pain, Imt, Sitting Time, Years Of Service. ABSTRAK Low Back Pain (LBP) dapat didefinisikan nyeri menetap diantara pinggang hingga lipatan bokong. LBP juga adalah salah satu dari PAK khususnya untuk pekerja. Penyebab LBP sangat luas dan sulit dideteksi, tetapi faktanya penyebab LBP di tempat kerja sebagian besar adalah masalah ergonomis atau posisi kerja yang salah. Berdasarkan hasil pengamatan pada saat melaksanakan kegiatan magang di PLTU Nii Tanasa Kendari, kejadian low back pain sering terdengar sebagai keluhan para pekerja yang bekerja dengan posisi duduk yang lama. Low back pain menjadi salah satu penyakit akibat kerja yang mendominasi oleh para pekerja di PLTU Nii Tanasa Kendari dan salah satu yang memiliki dampak yang cukup merugikan bagi perusahaan serta penderitannya, dengan terganggunya aktivitas saat bekerja, terganggunya konsenterasi saat bekerja, rasa nyeri punggung bagian belakang yang dirasakan saat bekerja, bahkan saat setelah berkerja. Jenis penelitian ini yaitu jenis penelitian kuantitatif dan merupakan penelitian analitik yang bersifat observasional. penelitian ini menggunakan rancangan penelitian cross sectional. Sampel penelitian sejumlah 87 orang. Data dijangkau dengan menciptakan kuesioner dianalisis dengan menggunakan uji Chi-square. Hasil penelitian menunjukkan bahwa ada hubungan antara posisi duduk dengan kejadian Low Back Pain (p=0,001), tidak ada kaitan antara lama duduk dengan kejadian Low Back Pain (p=0,297), tidak ada kaitan antara masa kerja dengan kejadian Low Back Pain (p=0,105), tidak ada kaitan antara IMT dengan kejadian Low Back Pain (p=0,451), dan tidak ada kaitan antara riwayat penyakit dengan kejadian Low Back Pain (p=0,791). Diharapkan kepada peneliti baru dapat lebih menggali terakit kejadian Low Back Pain. Kata Kunci: Nyeri Punggung Bawah, Imt, Lama Duduk, Masa Kerja.